INVESTIGATION OF PREHEAT TEMPRATURE EFFECT ON THE STURCTURE OF FUNCTIONALLY GRADED Ni3Al/NiAl/NiTi INTERMETALLIC COMPOUND - Kilic, Musa; Kirik, Ihsan; Kurt, Bulent; Orhan, Nuri (Pamukkale Univ, 2015)
In this study, a functional graded material (FGM) consisted of NiTi NiAl and Ni3Al were manufactured by self-propagating high-temperature synthesis (SHS) technique. These three different compound powders were mixed in a rotating container after accurately weighed and cold compacted under 200 MPa pressure. These pressed samples were produced for 200, 300 and 400 degrees C preheating temperature by igniting with high voltage under argon gas atmosphere. The microstructures of these functional graded materials were examined by microscopy, Scanning Electron Microscopy (SEM) and X-Ray Diffraction (XRD). Consequently, functional graded material successful generated by SHS in every three preheating temperature and the metallic desired compounds were obtained but, it was seen that apart from the main phases in the intersection there are other phases with more melting and gaps.
Keywords: FGM; SHS; NiTi; NiAl; Preheating temperature